Influence of Inflation, Investment and Population growth rate on Supply Chain Performance and Economic Growth of Indonesia - Reydonnyzar Moenek (International Journal of Supply Chain Management, 2020)
Abstract-  Extensive literature is available on supply chain performance (SCP). “Most of the studies examined the relationship between SCP and firm performance in both developed as well as developing countries. However, researchers did not consider the effect of SCP on economic growth, particularly in Indonesian prospective. Therefore, the objective of this study is to examine the role of supply chain performance in the economic growth of Indonesia. To address the objective, data were collected from Indonesian economists. E mail survey was used, and questionnaires were distributed to collect the data. A total number of seven hypotheses were tested with the help of the structural equation modeling technique. The finding shows that inflation has an influence on SCP. Increases in inflation decrease the SCP. Moreover, investment growth rate and population growth rate also have an effect on SCP which has a contribution to the economic growth of Indonesia. Thus, the Indonesian government must boost supply chain to enhance economic growth.